Rancang Bangun Pengaman Sepeda Motor Menggunakan RFID Berbasis Arduino - Muhammad Ridha Fauzi (Fakultas Teknik UMRI, 2020)
The safety of a motorcycle is very important for vehicle owners. Until now, most motorbikes still rely only on the key to contact the vehicle itself. In the case of vehicle theft, it is very easy for the perpetrator of the theft to use the letter